Complete Recovery from COVID-19 Bilateral Pneumonia in an Immunosuppressed Man with Immune-Mediated Necrotizing Myopathy - Thomas C. Bolig; Nada Abdulaziz; Elena Schiopu (Case Reports in Rheumatology)
Immune-mediated necrotizing myopathy (IMNM) is a rare form of idiopathic immune myopathy (IIM) that requires immunotherapies, including immunosuppressive medications, if severe. There is a paucity of data regarding outcomes of patients with immune-mediated polymyositis who continue immunosuppressive medications during the COVID-19 pandemic. This is the first reported case of COVID-19 in a patient with IMNM. Despite being on two immunotherapies, having risk factors, and having radiographic abnormalities on chest X-ray, the patient had an unremarkable COVID-19 course. He was discharged from the emergency department with a 7-day course of azithromycin and quickly resumed his immunotherapies, but he experienced a flare in his myositis. The 14-week follow-up computed tomography (CT) was negative for residual pneumonitis or fibrosis. More data are needed regarding management and prognosis of patients with connective tissue diseases who become infected with SARS-CoV-2.